Multisyllabic Word Reading as a Moderator of Morphological Awareness and Reading Comprehension. (January 2014) - Gilbert, Jennifer K.; Goodwin, Amanda P.; Compton, Donald L.; Kearns, Devin M.
The purpose of this study was to investigate whether the relation between morphological awareness on reading comprehension is moderated by multisyllabic word reading ability in fifth-grade students ( N = 169, 53.7% female, 65.2% minority status, 69.2% free/reduced lunch status), oversampled for poor reading skill, when controlling for general knowledge and vocabulary. Based on the lexical quality hypothesis, it was expected that morphological awareness would have a stronger effect on comprehension for children with poor word reading skills, suggesting possible use of morphological awareness for word identification support. Results indicated that neither morphological awareness nor word reading was uniquely associated with reading comprehension when both were included in the model along with vocabulary and general knowledge. Instead, the interaction between word reading and morphological awareness explained significant additional variance in reading comprehension. By probing this interaction, it was determined that the effect of morphological awareness on reading comprehension was significant for the 39% of the sample that had more difficulty reading multisyllabic words but not for students at the higher end of the multisyllabic word reading continuum. We conclude from these results that the relation between morphological awareness and reading comprehension is moderated by multisyllabic word reading ability, providing support for the lexical quality hypothesis. Although we have only correlational data, we suggest tentative instructional practices for improving the reading skill of upper elementary struggling readers.